GOVERNMENT ALIH SMA / SMK (Studi Tentang Persepsi Pendidik dan Tenaga Kependidikan di Kabupaten Pangkep) - Samad, Sulaiman; Anas, Muhammad (Pascasarjana Universitas Negeri Makassar, 2017)
This research is conducted based on the problems: (1) How is the perception of educator and education personnel in Pangkep regency about the planning of education program in implementation of SMA / SMK? (2) What is the perception of educators and education personnel in Pangkep District about the implementation of educational work plan in implementation of SMA / SMK? (3) What is the perception of educators and education personnel in Pangkep regency about supervision and evaluation of education activities in the implementation of high school / vocational transfer?. This research is done through quantitative approach with descriptive type. This research was conducted in SMA / SMK that exist in Pangkajene Kepulauan Regency of South Sulawesi Province. Population of this research is educator (teacher) and education staff of SMA / SMK which exist in Pangkajene Islands Regency. Simple sampling. To get the information then in this research used research instrument in the form of questionnaire (questionnaire) which is distributed to the respondent, in this case educator and education personnel in Pangkajene and Kepulauan.